Інформаційні сліди в контексті механізму вчинення злочинів із використанням обстановки кіберпростору - Самойленко, Олена Анатоліївна; Самойленко, Елена Анатольевна; Samoilenko, Olena A.; Паляничко, Діана Геннадіївна; Паляничко, Диана Геннадиевна; Palianychko, Diana H.; Баланюк, Олексій Валентинович; Баланюк, Алексей Валентинович; Ващенко, Ірина Олександрівна; Ващенко, Ирина Александровна; Balanyuk, Oleksii V.; Vaschenko, Iryna O. (Одеса, 2018)
Стаття присвячена значення інформаційних слідів злочинів в контексті механізму їх вчинення із використанням обстановки кіберпростору. Розглядаються питання щодо локалізації таких слідів та їх зв’язків з іншими елементами механізму злочину вказаної категорії.

Статья посвящена значению информационных следов преступлений в контексте механизма их совершения с использованием обстановки киберпространства. Рассматриваются вопросы локализации таких следов и их связей с другими элементами механизма преступления указанной категории.

The article is devoted to the value of information traces of crimes in the context of mechanism of their accomplishing with the use of crime scene cyberspace. The special character of information traces from positions of traditional criminalistics classification of traces of crimes is established. Informative tracеs is analyzed. The question of localization of such traces rises that results in establishment of presence of their communications with other elements of mechanism of crime of the explored category. It becomes firmly established that traces of crime in electronic space are reflected simultaneously in many vehicle facilities of computer technique, telecommunication network, network of elektrosvyazi. These vehicle facilities are physically found on certain geographical territory under jurisdiction of the certain state and in own of concrete man or organization. Information traces can confirm circumstance that access of criminal to the informative product/resource which is an object or instrument of criminal activity was provided by an oversea operator/provider. In this case it is necessary to speak about specific descriptions of personality of criminal in particular about his mobility professional, geographical or social, about his role in composition the organized criminal group, amount of participants of such group. An author comes to conclusion, that information traces of crime with the use of crime scene cyberspace form an informative basis which is used for cognition of mechanism of commission of concrete crime in cyberspac
Інформаційні сліди в контексті механізму вчинення злочинів із використанням обстановки кіберпростору / О. Самойленко, Д. Паляничко, О. Баланюк, І. Ващенко // Криміналістика та судова експертологія: наука, навчання, практика : матеріали XIV міжнар. Конгресу (м. Одеса, 13-15 верес.): у 2-х т. – Одеса : Гельветика, 2018. – т. 2. – С. 216-221.
Keywords: злочин; інформаційні сліди; кіберпростір; комп’ютер; місце злочину; нетрадиційні сліди; crime; information traces; cyberspace; computer; crime scene; unconventional traces; преступление; информационные следы; киберпространство; компьютер; место преступления